Unveiling the link between board gender diversity and energy firm’s performance in South Asia: the mediating role of earnings management - Majumder, Md. Tofael Hossain; Abdul Hamid, Mohamad Ali; Amin Noordin, Bany Ariffin; Al-Duais, Shaker (Cogent, 2024)
This paper attempts to shed light on an analytical model that examines both direct relationship between board gender diversity and energy firms’ performance and an indirect connection in which earnings management is a mediating variable that is affected by the board gender diversity, which in turn affects the performance of energy firms. This study employs a dynamic panel model with the two-step system generalized methods of moments (system GMM) technique using 77 listed energy firms of South Asian emerging economies (i.e. Bangladesh, India, & Pakistan) covering from 2015 to 2019. The findings show that gender diversity significantly and positively impacts energy firms’ performance in South Asia. The study results also find that earnings management plays a complementary mediating role (i.e. partial mediation) in the association between gender diversity and energy firms’ performance. This research demonstrates the economic value of having female directors on corporate boards by strengthening companies’ governance structure and decreasing earnings management. On the issue of board gender diversity policy, this research offers vital practical information for South Asian regulators, particularly in the energy sector. The present study is a novel study on the emerging South Asian energy sector that contributes to the literature for the first time by exploring the nexus between board gender diversity and firm performance with the mediating role of earnings management, which the previous literature has overlooked.